Unsur Lokalitas dalam Tafsir Berbahasa Bugis Karya AGH. Daud Ismail (Studi Analisis Psychological Hermeneutics terhadap QS. Al-Maidah 5:90) - Winceh Herlena; Muads Hasri (El-Afkar: Jurnal Pemikiran Keislaman dan Tafsir Hadis, 2020)
Indonesian mufassir generally use Indonesian in interpreting the Al-Qur'an. However, the interpretation of AGH Daud Ismail uses the script lontara bugis to interpret the Al-Qur'an 30 Juz. Therefore, the author tries to see the aspects behind the use of the lontara script in the interpretation of AGH Daud Ismail.In addition, the author will also explore the locality elements shown in Daud Ismail's interpretation of the QS. Al-Maidah 5:90.This paper uses Schleiermacher's hermeneutic approach on psychological hermeneutics with a descriptive-analytic method.This paper concludes that: first, the use of the lontara script in this interpretation is an attempt to preserve the Bugis script which has begun to be abandoned at that time; second, in the interpretation of QS. Al-Maidah 5:90 contains terms and habits that exist in the Bugis community.